Cyprus as AI Saw it: Reinventing the Colonial Gaze - Koutsomichalis, Marinos; Achilleos, Alexia (My University, 2021)
‘Cyprus as AI Saw it: Reinventing the Colonial Gaze’ is part of ‘Cyprus as AI Saw it’, a wider artistic project thematic concerned with decolonial re-interpretations of the island’s history. The endeavour employs an AttnGAN text-to-image generation model and a RNN text generator. The latter is trained on text from colonial handbooks of Cyprus, originally published when Cyprus was still part of the British Empire and reflecting an overly orientalist gaze of the (then) newly annexed British colony. Cyprus is presented therein as a degenerate country whose people are in urgent need of salvation. Trained on such a corpus, the model may then generate new colonial descriptions of Cyprus. These then become the input of a GAN-driven text-to-image pipeline. This subsystem relies on a bespoke dataset that is meant to reflect the local reality since, not surprisingly, the readily available image databases largely fail to account for Eastern Mediterranean landscapes/culture (they generally produce images that are more reminiscent of the Western cities that host the big tech companies that distribute them).